Development of Roselle (Hibiscus sabdariffa L.) Transcriptome-Based Simple Sequence Repeat Markers and Their Application in Roselle - Aifen Tao; Yunqing Li; Jihan Chen; Jing Li; Jiantang Xu; Lihui Lin; Liwu Zhang; Pingping Fang (Plants)
Roselle (Hibiscus sabdariffa L.) simple sequence repeat (SSR) markers were developed using RNA sequencing technology, providing a foundation for genetic analysis and the identification of roselle varieties. In this study, 10 785 unigenes containing 12 994 SSR loci with an average of one SSR locus per 6.87 Kb were identified, and the occurrence frequency of the SSR loci was 11.36%. Trinucleotide repeat motifs were the most abundant, followed by dinucleotide repeats, with AAG/CTT and AT/AT being the predominant types, respectively. After screening 100 primer pairs with a polymorphic ratio of 32.0%, we obtained 32 primer pairs, resulting in clear and stable polymorphic bands. Twenty-seven primer pairs were highly or moderately polymorphic, and seven primer pairs were highly polymorphic. Genetic relationship analysis based on the selected SSR primers showed that 38 roselle accessions were classified into different clades, with those from the same regions clustered into the same subgroups. In contrast, individuals with unique morphological traits were separated. DNA fingerprints of 38 roselle varieties were constructed using five SSR primers, providing an effective method for identifying roselle varieties at a molecular level. Our data provide novel insights into the genetics of H. sabdariffa and may be used in SSR-assisted roselle breeding.